Remdesivir (GS-5734) Is Efficacious in Cynomolgus Macaques Infected With Marburg Virus. (1st June 2020) - Porter, Danielle P; Weidner, Jessica M; Gomba, Laura; Bannister, Roy; Blair, Christiana; Jordan, Robert; Wells, Jay; Wetzel, Kelly; Garza, Nicole; Van Tongeren, Sean; Donnelly, Ginger; Steffens, Jesse; et al.
Abstract: Marburg virus (MARV) is a filovirus with documented human case-fatality rates of up to 90%. Here, we evaluated the therapeutic efficacy of remdesivir (GS-5734) in nonhuman primates experimentally infected with MARV. Beginning 4 or 5 days post inoculation, cynomolgus macaques were treated once daily for 12 days with vehicle, 5 mg/kg remdesivir, or a 10-mg/kg loading dose followed by 5 mg/kg remdesivir. All vehicle-control animals died, whereas 83% of animals receiving a 10-mg/kg loading dose of remdesivir survived, as did 50% of animals receiving a 5-mg/kg remdesivir regimen. Remdesivir-treated animals exhibited improved clinical scores, lower plasma viral RNA, and improved markers of kidney function, liver function, and coagulopathy versus vehicle-control animals. The small molecule remdesivir showed therapeutic efficacy in this Marburg virus disease model with treatment initiation 5 days post inoculation, supporting further assessment of remdesivir for the treatment of Marburg virus disease in humans. Abstract : The small molecule remdesivir (GS-5734) showed therapeutic efficacy in a nonhuman primate model of Marburg disease with treatment initiation 5 days post inoculation, supporting further assessment of remdesivir for the treatment of Marburg virus disease in humans.